Persuasive Communication Of Health Workers In Handling The Corporation Of The Covid-19 On A Covid-19 Referral Hospital - Doni Zamroni (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Persuasive communication of health workers to patient families in handling Covid-19 bodies at the Covid-19 Referral Hospital (Hope and Prayer Hospital, Bengkulu City). In this study, the method used is qualitative. The selection of informants for this study was taken using a purposive sampling technique, namely: Covid-19 task force officers, families of patients or family relatives of patients who died and officials of the Covid-19 Referral Hospital. Qualitative data analysis in the form of data reduction, data presentation, and drawing conclusions and verification. The results of the persuasive communication research by health workers to patient families in handling Covid-19 corpses at the Covid-19 referral hospital at Harapan and Prayer Hospital in Bengkulu City have not been maximized because health workers have not been equipped with expertise and in providing good explanations for patient families and poor communication. still doing normally. Suggestions to the Hope and Prayer Hospital of Bengkulu City should provide training to health workers, especially officers related to the delivery of good communication to the patient's family in handling the recovery of Covid 19 bodies, and should be able to make Standard Operating Procedures (SOP) ) related to the delivery of good communication to the family of patients in the handling of Covid-19 corpses and should be able to create a special room related to the delivery of communication to the patient's family in handling Covid-19 corpses.